A comercialização da produção agrícola no município de Piedade (SP) - Fernandes, Erik Romano [UNESP] (2011)
The adoption of neoliberal policies in Brazil in the 1990s reduced the State's participation in several productive activities, including food production and distribution. It made it possible to operate private networks, including foreign, as well as growing marketing of fruit and vegetables. The town of Piedade (SP) has contributed a lot to food supply in the state of São Paulo. Some facts took places in the early 1990s, such as the onion crop crisis, the Green Belt of the Metropolitan Region of São Paulo expansion, the reducing State participation and the increasing private capital participation caused significant changes in the fruit and vegetable production chain: from production to the end consumer. The aim of this paper is to clarify how the fruit and vegetable marketing works in Piedade and also to explain the producers' dependence on different agents to sell their products to the consumer centers.